[Two Black attendees of MLK event] (1993)
The person on the left, appearing to be over the age of 40, is greeting the younger student on the left. They are in the University Union plaza, in front of the bookstore. The student is wearing a shirt with an illustration of Martin Luther King Jr.'s face, a California Angels jacket, and hat with an 'X' on it (possibly for Malcolm X). The older person is wearing a cap similar in style to an ivy cap, and a sweater with several patters on it.